Covalent immobilization of glucose oxidase on amino MOFs via post-synthetic modification. Issue 109 (11th November 2016) - Tudisco, C.; Zolubas, G.; Seoane, B.; Zafarani, H. R.; Kazemzad, M.; Gascon, J.; Hagedoorn, P.-L.; Rassaei, L.
Abstract : Post Synthetic Modification (PSM) of amino-metal organic frameworks (NH2 -MOFs) with the enzyme Glucose Oxidase (GOx) is reported. Abstract : The post-synthetic modification (PSM) of two amino-MOFs with glucose oxidase is reported in this study. The multi-step approach preserved the MOFs' structure and allowed the production of enzyme-functionalized MOFs (MOFs@GOx), which retained the enzymatic activity and showed selective properties for glucose.